2021
DOI: 10.1002/ajh.26203
|View full text |Cite
|
Sign up to set email alerts
|

Reduced global cerebral oxygen metabolic rate in sickle cell disease and chronic anemias

Abstract: Anemia is the most common blood disorder in the world. In patients with chronic anemia, such as sickle cell disease or major thalassemia, cerebral blood flow increases to compensate for decreased oxygen content. However, the effects of chronic anemia on oxygen extraction fraction (OEF) and cerebral metabolic rate of oxygen (CMRO 2 ) are less well understood. In this study, we examined 47 sickle-cell anemia subjects (age 21.7 ± 7.1, female 45%), 27 non-sickle anemic subjects (age 25.0 ± 10.4, female 52%) and 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 93 publications
(205 reference statements)
3
23
0
Order By: Relevance
“…The observations of increased OEF by Fields et 2 This study also found that OEF in anemic controls differed from healthy controls and SCA had even larger OEF differences, however, the differences were in the opposite direction with SCA having the lowest OEF. This discrepancy could lead readers to dismiss both methods, not knowing which is correct, but once the details of each measurement technique are considered a reconciliation between these opposite observations is possible.…”
supporting
confidence: 63%
“…The observations of increased OEF by Fields et 2 This study also found that OEF in anemic controls differed from healthy controls and SCA had even larger OEF differences, however, the differences were in the opposite direction with SCA having the lowest OEF. This discrepancy could lead readers to dismiss both methods, not knowing which is correct, but once the details of each measurement technique are considered a reconciliation between these opposite observations is possible.…”
supporting
confidence: 63%
“…T 2 -based MR oximetry such as TRUST MRI has been exploited widely due to its non-invasive property, less model assumption, short scan time and high reproducibility (Lu and Ge, 2008;Lu et al, 2012;Xu et al, 2012;Jiang et al, 2018Jiang et al, , 2021. However, inconsistent results have been reported on whether OEF and CMRO 2 are increased, decreased or unaffected in sickle cell disease (Jordan et al, 2016;Bush et al, 2018bBush et al, , 2021Juttukonda et al, 2019Juttukonda et al, , 2020Li et al, 2020;Václavů et al, 2020;Prussien et al, 2021;Vu et al, 2021) The original bovine model was derived from bovine blood, which is thought to have similar magnetic properties as normal human blood (Lu et al, 2012). However, it was also speculated that the bovine model was calibrated in a relatively small hematocrit range (35-55%), which is much higher than the hematocrit level in SCD (Lu et al, 2012;Bush et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…One is T 2 -based oximetry, based on the principle that oxygen content in the blood can alter the blood T 2 due to its magnetic property (Wright et al, 1991;Silvennoinen et al, 2003;Zhao et al, 2007;Lu and Ge, 2008;Lu et al, 2012). Several studies have been conducted in SCD patients to investigate the role of OEF and CMRO 2 using the T 2 -based method (Jordan et al, 2016;Bush et al, 2018bBush et al, , 2021Morris et al, 2018;Vaclavu et al, 2018;Juttukonda et al, 2019Juttukonda et al, , 2020Li et al, 2020;Václavů et al, 2020;Prussien et al, 2021;Vu et al, 2021); however, the results of these studies are variable, largely due to the calibration models used to convert venous blood T 2 to venous oxygenation (Y v ). Using a bovine blood model, Jordan et al (2016) reported increased OEF and CMRO 2 in SCD; however, it has been speculated that the bovine model may not be suitable for sickled blood, due to a much lower hematocrit range and different size, shape, and permeability of the sickled blood cell (Clark and Rossi, 1990;Gibson and Ellory, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have investigated OEF changes in SCD but reported inconsistent results. Several groups have measured global OEF in SCD using T 2 -based techniques, 5,54,81,235,[252][253][254][255][256][257] but the OEF results varied when different calibration models were used to convert blood T 2 to Y v (see Section 3.1.2). 258 Studies using the bovine calibration model 43 showed that OEF was higher in SCD patients than controls, 235,252 and OEF was reduced after blood transfusion.…”
Section: Sickle Cell Diseasementioning
confidence: 99%